ENDODONTIC-PERIODONTAL LESION: A CASE REPORT - Zanella, Dionatan; Bonezi Boff, Luiza; Pereira Butze, Juliane (Health and Society, 2023)
Introduction: Periodontal and pulp tissues are closely related through communication pathways present in the periodontium. This interrelation supports the emergence of endo-periodontal lesions, caused by infectious and irritating products, triggering an inflammatory response Objective: The present study aim to report the treatment of a case of endo-periodontal lesion where endodontic treatment was performed prior to periodontal treatment. Case description: On clinical and radiographic examination, the patient was diagnosed with an endo-periodontal lesion on element 48. The proposed treatment plan was endodontics followed by subgingival scaling. Conclusion: Endodontic treatment associated with periodontal treatment led to the resolution of the case, being observed the absence of pain, absence of abscess/fistula, decreased probing depth and tooth mobility, in addition to bone gain seen radiographically.